2020
DOI: 10.1080/09603123.2020.1788712
|View full text |Cite
|
Sign up to set email alerts
|

A cluster-randomised trial to evaluate an intervention to promote handwashing in rural Nigeria

Abstract: Handwashing with soap at critical times helps prevent diarrhoeal diseases. Changing handwashing practices through behaviour change communication remains a challenge. This study designed and tested a scalable intervention to promote handwashing with soap. A cluster-randomised, controlled trial compared our intervention against standard practice. Subjects were men, women and children in 14 villages in Cross-River state, Nigeria. The primary outcome was the proportion of observed key events on which hands were wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…During that first modest increase (2010 – 2017), 12 studies were published [39, 41, 46, 49, 56, 59-61, 63-65, 67]. The exponential increase is most noticeable in 2018 resulting in 7 eligible studies [42, 43, 48, 50, 55, 57, 58], while in 2019, there were 9 included studies [38, 44, 45, 52, 54, 62, 66, 69, 70], and finally up until 6 th September 2020 we identified 5 additional studies [40, 47, 51, 53, 68].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…During that first modest increase (2010 – 2017), 12 studies were published [39, 41, 46, 49, 56, 59-61, 63-65, 67]. The exponential increase is most noticeable in 2018 resulting in 7 eligible studies [42, 43, 48, 50, 55, 57, 58], while in 2019, there were 9 included studies [38, 44, 45, 52, 54, 62, 66, 69, 70], and finally up until 6 th September 2020 we identified 5 additional studies [40, 47, 51, 53, 68].…”
Section: Resultsmentioning
confidence: 99%
“…One study was conducted in both Bangladesh and Kenya [60]. The other half of the included studies were conducted in Africa (15 records): four studies in Kenya [52, 55, 66, 70], followed by two in Zimbabwe [53, 56], Nigeria [40], South-Africa [42], Malawi [45], Ethiopia [46], Chad [58], Burundi [61], Zambia [62], Mali [64], Egypt [65], and Uganda [67]. Finally, only one study was identified which took place on the South-American continent: Peru [43].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations